Physical rehabilitation in scoliotic spine injuries in children suffering from cerebral palsy - V.G. Kalogerova; Yu.A. Gryshun; O.M. Korchak; E.A. Bulkina (Pedagogics, Psychology, Medical-Biological Problems of Physical Training and Sports, 2013)
The results of the effectiveness of physical rehabilitation programs for children with cerebral palsy with scoliosis spinal lesion. The study involved 20 children aged 5-6 years. Diagnosis of motor function of children assessed to determine the strength endurance of back muscles and abdominals. The angle of curvature of the spine was measured on a scale Chaklin. The reaction of the cardiovascular system load was determined using a sample Shalkova and oxygen supply of the body - the breakdown of the Stange and Genchi. For improvement of lung function and cardio-respiratory systems of children are used with breath exercises and training of diving in the pool. It is established that the introduction of a game program "In the world of animals" and holding corrective exercises in the pool has a positive effect on the functional state of the spine, the cardiorespiratory system and the physical development of children.